Papain-like cysteine proteases as hubs in plant immunity - Misas-Villamil, J; van der Hoorn, R; Doehlemann, G (Wiley, 2016)
Plants deploy a sophisticated immune system to cope with different microbial pathogens and other invaders. Recent research provides an increasing body of evidence for papain-like cysteine proteases (PLCPs) being central hubs in plant immunity. PLCPs are required for full resistance of plants to various pathogens. At the same time, PLCPs are targeted by secreted pathogen effectors to suppress immune responses. Consequently, they are subject to co-evolutionary host-pathogen arms race. When activated, PLCPs induce a broad spectrum of defense responses including plant cell death. While the important role of PLCPs in plant immunity has become more evident, it remains largely elusive how these enzymes are activated and which signaling pathways are triggered to orchestrate different downstream responses.